2021
DOI: 10.1002/bse.2766
|View full text |Cite
|
Sign up to set email alerts
|

Which are the determinants of green purchase behaviour? A study of Italian consumers

Abstract: Green purchase behaviour is receiving a growing attention in the academic community, as understanding it is crucial for the growing number of companies developing and marketing green products. In order to provide a broader and novel picture of the phenomenon, this study extends the widely used Theory of Planned Behaviour (TPB) model in several ways, through a large survey of Italian consumers. First, three dimensions of green purchase behaviour are considered, namely, the willingness to pay a premium price, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 111 publications
(202 reference statements)
6
78
0
Order By: Relevance
“…Finally, future research should examine other potential personal or situational factors that can influence consumers' loyalty toward green products/services. [9,43,60] INN2: I am willing to try new things INN3: I am eager to buy new products as soon as they come out INN4: Others often ask me for advice about new products Self-Accountability SA1: I feel accountable if meaningful damage to the environment occurs in the coming year [50] SA2: I am accountable for protecting the environment SA3: I feel accountable to my own self-standards Attitude ATT1: I feel positive toward the green credit card services [61] ATT2: The green credit card services are good ATT3: I like the green credit card services…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, future research should examine other potential personal or situational factors that can influence consumers' loyalty toward green products/services. [9,43,60] INN2: I am willing to try new things INN3: I am eager to buy new products as soon as they come out INN4: Others often ask me for advice about new products Self-Accountability SA1: I feel accountable if meaningful damage to the environment occurs in the coming year [50] SA2: I am accountable for protecting the environment SA3: I feel accountable to my own self-standards Attitude ATT1: I feel positive toward the green credit card services [61] ATT2: The green credit card services are good ATT3: I like the green credit card services…”
Section: Discussionmentioning
confidence: 99%
“…Respondents' action-based knowledge was measured by assessing their familiarity with the term "carbon labelling" (one item). Innovativeness was measured using four items adapted from previous studies [9,43,60]. Self-accountability was measured using a three-item scale provided by Peloza et al [50].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall product satisfaction is a prerequisite for recurring behavior and sales, as well as for recommendations to convince others of the quality and value of more sustainable products. Dangelico et al [12] showed the mediating effect of green purchase satisfaction on the links between personal norms and green purchase frequency. They highlighted the relevance of considering purchase satisfaction when studying green purchase behavior, although this has received limited attention in the past.…”
Section: Product Recommendationsmentioning
confidence: 99%